THE CLASH OF SUFI AND SALAFIST EDUCATION ON INDONESIAN FACEBOOK - Ishak Wanto Talibo; Wasisto Raharjo Jati; Almunawar Bin Rusli (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2025)
This article examines the Facebook-based educational debate between Sufi scholar Ulil Abshar Abdalla and Salafi scholar Yazid bin Abdul Qadir Jawas. Our research addresses three main questions: What educational philosophies do Sufis use to defend against Salafi attacks? What educational approach does Salafis use to refute Sufi’s critiques? How does this theological conflict affect the daily religious practices of Indonesian Muslims? Using Facebook Analytics, this study analyzes recordings from the online Ngaji Ihya and Ngaji Rodja groups. The analysis comprises the coding of images and non-text data, a narrative analysis of social media content, and an examination of audience behaviour. Our research indicates Ulil Abshar Abdalla’s Sufism is a culturally-based approach to overcoming Islamic sectarian divisions within Indonesia. Yazid bin Abdul Qadir Jawas’s Salafist ideology, rooted in textual fiqh, is used to undermine Indonesia’s moderate Islamic voices. The conflict between the two groups stems from disagreements about faith, rituals, democracy, and customs. This theological conflict has resulted in both inclusive and exclusive religious practices. Facebook has become a battleground for competing Sufi and Salafi Islamic viewpoints. Sufism’s defensive position is characterized by its inclusivity and multiple perspectives, unlike salafism’s confrontational and singular view.